Inferno of choices : Poles and the Holocaust - Rejak, Sebastian; Frister, Elżbieta, 1949- (Warsaw : Oficyna Wydawnicza RYTM, 2012)
This second, expanded edition portrays the present state of academic research and public debate on wartime Polish-Jewish history which goes on regardless of the controversies and the trauma both sides have to face. The first edition was published by Oficyna Wydawnicza RYTM in 2011. Two new chapters have been provided for this edition.
Keywords: Holocaust, Jewish (1939-1945) -- Poland; Holocaust, Jewish (1939-1945) -- Historiography; Holocaust -- Jews -- Poland -- Nazis